Activity of lipid-soluble inhibitors of dihydrofolate reductase against Pneumocystis carinii in culture and in a rat model of infection. - Queener, S F (1987)
Trimetrexate and BW301U (piritrexim isethionate), lipid-soluble inhibitors of dihydrofolate reductase, are potent inhibitors of the growth of Pneumocystis carinii in culture with WI-38 cells. Inhibition was observed with 0.1 microgram of trimetrexate or BW301U per ml. Trimethoprim is ineffective at 100 micrograms/ml in this culture system. Both trimetrexate and BW301U were effective as prophylactic agents against P. carinii pneumonia in rats; trimetrexate at 7.5 mg/kg protected 9 of 10 rats, and BW301U at 5 mg/kg protected 4 of 10.